The Sir Hugh Laddie Lectures the first ten years - Jacob, Robin 1941- (Intersentia, 2019)
This volume is a compendium of the Sir Hugh Laddie Lectures delivered at University College London (UCL) in the period between 2009 and 2018. This is a public lecture series organised by the Institute of Brand and Innovation Law (IBIL) at UCL Faculty of Laws in honour of IBIL's founder - Professor Sir Hugh Laddie. Presented as a collection of verbatim lecture transcripts, rather than formal papers, the book brings the subjects to life by providing the reader with a 'fly on the wall' experience. As distinguished IP judges, academics and policy makers, the eminent men and women who gave these lectures have all played a prominent role in shaping the recent development of intellectual property law. The lecture forum affords them the opportunity to speak in a personal capacity, often with surprising candour, which casts what may seem well-worn subject matter in a new and interesting light.
Title from publisher's bibliographic system (viewed on 08 Nov 2019)
Keywords: Intellectual property